ANALISIS PERBEDAAN SISTEM PENYULUHAN PERTANIAN PADA MASA SEBELUM DAN SELAMA PANDEMI COVID-19 DI KABUPATEN MALANG - Laily Ana Fauziah; Eri Yusnita Arvianti; Dyanasari Dyanasari (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2024)
The agricultural extension system is a whole series of development of abilities, knowledge, skills and attitudes of main actors and business actors through extension. The agricultural extension system in Indonesia has experienced quite dynamic ups and downs since the COVID-19 pandemic hit this country. The extension system has changed in line with the policies taken by the government in response to Covid-19. This research aims to determine the effect of differences in agricultural extension systems before and during COVID-19 in the Malang Regency. This research method is descriptive qualitative with data analysis using Structural Equation Modeling. The research analysis results show significant differences in the agricultural extension system before and during COVID-19 in Malang Regency. During the pandemic, there have been significant changes in agricultural extension methods. Online methods and information technology are increasingly dominant, while face-to-face meetings have decreased drastically. Even though online methods are increasing, there are challenges in information accessibility for some farmers, especially farmers who live in rural areas with limited technological infrastructure. Farmer participation in extension activities tends to decrease during the pandemic. Factors such as technological limitations, unstable internet connections, and difficulty understanding online material are the main causes. The Covid-19 pandemic has also had a significant economic impact on farmers. The main challenges faced by farmers during the pandemic are limited market access, increasing prices of agricultural inputs, and decreasing selling prices for agricultural products.